Single immunization with a suboptimal antigen dose encapsulated into polyanhydride microparticles promotes high titer and avid antibody responses1. Issue 1 (10th November 2012) - Huntimer, Lucas; Wilson Welder, Jennifer H.; Ross, Kathleen; Carrillo‐Conde, Brenda; Pruisner, Lynn; Wang, Chong; Narasimhan, Balaji; Wannemuehler, Michael J.; Ramer‐Tait, Amanda E.
Abstract: Microparticle adjuvants based on biodegradable polyanhydrides were used to provide controlled delivery of a model antigen, ovalbumin (Ova), to mice. Ova was encapsulated into two different polyanhydride microparticle formulations to evaluate the influence of polymer chemistry on the nature and magnitude of the humoral immune response after administration of a suboptimal dose. Subcutaneous administration of a single dose of polyanhydride microparticles containing 25 μg of Ova elicited humoral immune responses that were comparable in magnitude to that induced by soluble doses of 400–1600 μg Ova. In contrast, the avidity of the Ova‐specific antibodies was greater in mice administered the microparticle formulations in comparison to the higher soluble doses. Finally, the microparticle delivery system primed an anamnestic immune response as evidenced by the significant increases in Ova‐specific antibody when mice were administered an antigenic challenge of 25 μg of Ova at 12 weeks post‐vaccination. Together, these results indicate that encapsulation of antigens into polyanhydride microparticles facilitates isotype switching, establishes immunologic memory, and the humoral response was characterized by a higher quality antibody response. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 101B: 91–98, 2013.